2, 4-Bis(4-aryl-1, 2, 3-triazol-1-yl)pyrrolo[2, 3-d]pyrimidines: synthesis and tuning of optical properties by polar substituents1. Issue 48 (28th May 2015) - Bucevicius, Jonas; Skardziute, Lina; Dodonova, Jelena; Kazlauskas, Karolis; Bagdziunas, Gintautas; Jursenas, Saulius; Tumkevicius, Sigitas
<x xml:space="preserve">Abstract</x> Novel D–π–A–π–D type chromophores – 2, 4-bis(4-aryl-1, 2, 3-triazol-1-yl)pyrrolo[2, 3-d]pyrimidines were prepared and their photophysical, electrochemical properties in conjunction with quantum chemical calculations were investigated.